Regulation of invasive cell behavior by taiman, a Drosophila protein related to AIB1, a steroid receptor coactivator amplified in breast cancer. - Bai, J.; Uehara, Y.; Montell, D.J. (Cell, 2000)
Steroid hormones are key regulators of numerous physiological and developmental processes, including metastasis of breast and ovarian cancer. Here we report the identification of a Drosophila gene, named taiman, which encodes a steroid hormone receptor coactivator related to AIB1. Mutations in tai caused defects in the migration of specific follicle cells, the border cells, in the Drosophila ovary. Mutant cells exhibited abnormal accumulation of E-cadherin, beta-catenin, and focal adhesion kinase. TAI protein colocalized with the ecdysone receptor in vivo and augmented transcriptional activation by the ecdysone receptor in cultured cells. The finding of this type of coactivator required for cell motility suggests a novel role for steroid hormones, in stimulating invasive cell behavior, independent of effects on proliferation.